Biocatalytic synthesis of starch esters by immobilized lipase on magnetic microparticles. Issue 11 (2nd November 2015) - Prasertpornsakun, Nattanun; Raita, Marisa; Laosiripojana, Navadol; Champreda, Verawat
Abstract: Enzymatic esterification is an efficient approach for modifying starch to functionalized biomaterials. In this study, conversion of cassava starch to fatty acid acyl esters using immobilized Thermomyces lanuginosus lipase on Fe3 O4 microparticles modified with 3-aminopropyltriethoxysilane and covalently linked by 1-ethyl-3-(3-dimethyl aminopropyl) carbodiimide and N-hydroxysuccinimide (Fe3 O4 -AP-ED-lipase) in a solvent-free system was studied. An optimized reaction containing 5% w/v gelatinized starch, 1% v/v Triton X-100, and 1% w/v biocatalyst with 2.5% w/v of fatty acids (palmitic, oleic, or linoleic acid) resulted in esterified products with a degree of substitution (DS) of 0.12–0.14, while a slightly lower DS was observed using crude palm fatty acid distillate as the acyl donor with 42.9–59.6% recovery yield. Increasing DS led to lower glass transition temperature and higher viscosity of the esterified products. The enzyme showed high operational stability with 85% retaining in activity after recycling in three consecutive batches with simple separation by magnetization, leading to improved process economics. Graphical abstract: : Effects of acyl donors on esterification of starch. The reaction contained 5% gelatinized starch, 2.5% acyl donor, 1% Triton X-100 with 1% enzyme dosage and incubated at 50 °C, pH 7.0 for 24 h with stirring speed at 200 rpm.